BATF alleviates ox-LDL-induced HCAEC injury by regulating SIRT1 expression in coronary heart disease. - Bei Tian; Jingyu Ji; Can Jin (PLoS ONE)
Background Coronary heart disease (CHD) represents a significant global health concern, arising from an intricate interplay between genetic predisposition and environmental influences, with a pivotal involvement of oxidized low-density lipoprotein (ox-LDL) in the pathophysiology of it. We aimed to elucidate the synergistic dynamics of B cell activating transcription factor (BATF) and Sirtuin 1 (SIRT1) in cell injury caused by ox-LDL, reveal potential therapeutic strategies for CHD. Methods The GSE42148 dataset was used to analyze Differentially expressed genes (DEGs) to construct a gene co-expression network. Then bioinformatics analysis was performed on key modules to select the BATF gene. In vitro experiments were conducted to investigate the protective impact of BATF against human coronary artery endothelial cells (HCAEC) injury induced by ox-LDL. Further investigations probed the synergistic impact of BATF and SIRT1 modulation on cellular apoptosis and damage in the presence of ox-LDL. Results BATF was significantly down-regulated in the CHD sample of the GSE42148 dataset. In vitro assays have proven that BATF alleviates ox-LDL-induced HCAEC injury. Notably, BATF emerged as a pivotal regulator of SIRT1 expression post ox-LDL exposure. Subsequent experiments underscored the interplay between BATF and SIRT1 in mitigating ox-LDL-induced apoptosis and Lactate Dehydrogenase (LDH) activity elevation, highlighting their collaborative role in cellular protection. Conclusion The research findings suggested a prospective protective function of BATF in HCAEC injury induced by ox-LDL, likely through the mediation of SIRT1 regulation. These results could offer fresh perspectives on the etiology of CHD and possible treatment avenues.